Recent prospective of surface engineered Nanoparticles in the management of Neurodegenerative disorders. (2nd April 2016) - Singh, Devendra; Kapahi, Himani; Rashid, Muzamil; Prakash, Atish; Majeed, Abu Bakar Abdul; Mishra, Neeraj
Abstract : Clinically, the therapeutic outcomes in neurodegenerative disorders (NDs) by drug treatment are very limited, and the most insurmountable obstacle in the treatment of NDs is the blood–brain barrier (BBB), which provides the highest level of protection from xenobiotics. A great deal of attention still needs to be paid to overcome these barriers, and surface-engineered polymeric nanoparticles are emerging as innovative tools that are able to interact with the biological system at a molecular level for the desired response. The present review covers the potential importance of surface-structure-engineered nanoparticles to overcome the BBB for good bioavailability, and the evaluation of drug therapy in NDs.